2006
DOI: 10.1007/s10495-006-3391-4
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide FMRFamide can protect cells against apoptosis in the snail digestive gland

Abstract: FMRFamide-related peptides are widespread neurotransmitters or neurohormones regulating somatic or visceral motor activity. Some recent data indicate that these neuropeptides may be involved in the control of cell proliferation and apoptosis. In this work we investigated the possible effect of FMRFamide on cell viability in an invertebrate-type proliferating tissue. As a model, we used the midintestinal gland of the snail, Helix lucorum Linnaeus. Immunohistochemistry demonstrated the direct innervation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…PrRP is also found to influence human lymphocyte proliferation ( 153 ). In invertebrates, FMRFa has been found to inhibit apoptosis in a snail, indicating that the link between RFa and apoptosis is an evolutionary conserved mechanism ( 154 ). Interestingly, NPFF gene expression in mammals is regulated by transcription factors also involved in cell-cycle regulation and apoptosis ( 155 ).…”
Section: Discussionmentioning
confidence: 99%
“…PrRP is also found to influence human lymphocyte proliferation ( 153 ). In invertebrates, FMRFa has been found to inhibit apoptosis in a snail, indicating that the link between RFa and apoptosis is an evolutionary conserved mechanism ( 154 ). Interestingly, NPFF gene expression in mammals is regulated by transcription factors also involved in cell-cycle regulation and apoptosis ( 155 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that apoptosis in molluscs occurs not only during embryogenesis and metamorphosic development (Gifondorwa and Leise 2006), but it is a physiological phenomenon upon exposure to toxicants and other environmental stressors (Chabicovsky et al 2004;Gaitanaki et al 2004;Kefaloyianni et al 2005;Labieniec and Gabryelak 2007;Roszer et al 2006;Russo and Madec 2007). Caspase-like activity has also been described as essential for synaptic plasticity in Helix pomatia (Bravarenko et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of the PACAP is not unique, because it was reported that molluscan endogenous peptide FMRFa exerted a similar action on the midintestinal gland of the snail, Helix lucorum, indicating that FMRFa may be involved in the control of cell proliferation and apoptosis [46]. Cell cycle analysis revealed that FMRFa significantly elevated the number of cells in G 0 /G 1 phase, but did not induce mitosis.…”
Section: Salivation (Secretion)mentioning
confidence: 96%